1966
DOI: 10.1085/jgp.49.5.977
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of Sodium Conductance Increase in Lobster Giant Axon by Tarichatoxin (Tetrodotoxin)

Abstract: A~STRACT Tarichatoxin, isolated from California newt eggs, has been found to selectively block the increase of sodium conductance associated with excitation in lobster giant axons at nanomolar concentrations. This resulted from a reduction in the amplitude of the conductance increase rather than a change in its temporal characteristics. The normal potassium conductance increase with depolarization is not altered. A high concentration of calcium applied concomitantly with the toxin significantly improves the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

1967
1967
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(54 citation statements)
references
References 17 publications
(9 reference statements)
5
49
0
Order By: Relevance
“…The gate is probably controlled by membrane potential and calcium (Goldman, 1964). High external calcium concentration has been shown to interact with the blocking action of T T X (Takata et al, 1966), and this is consistent with the above mentioned notion.…”
Section: The M a X I M U M Values F O R T H E Early T R A N S I E N Tsupporting
confidence: 80%
See 2 more Smart Citations
“…The gate is probably controlled by membrane potential and calcium (Goldman, 1964). High external calcium concentration has been shown to interact with the blocking action of T T X (Takata et al, 1966), and this is consistent with the above mentioned notion.…”
Section: The M a X I M U M Values F O R T H E Early T R A N S I E N Tsupporting
confidence: 80%
“…Procaine differs from T T X not only in this nonselective blockage but also in its much higher threshold concentration and its effect on the kinetics of the early transient conductance increase (Takata et al, 1966).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This steady hyperpolarization (lobster axon resting potentials average about -7 0 mv in the absence of a sucrose gap) which normally occurs under a sucrose gap (Julian et al, 1962 a;Blaustein and Goldman, 1966 b) may be expected to minimize resting sodium inactivation. Takata et al (1966, Fig. 4) have shown that in the lobster giant axon under a sucrose gap, the resting sodium inactivation in normal artificial seawater is negligible at holding potentials greater than -100 m y .…”
Section: Is the Reduced Sodium Conductance A Manifestation Of Increasmentioning
confidence: 92%
“…To develop additional evidence that inhibition of Na + currents is the likely mechanism of action we also studied riluzole, an agent approved for the treatment of ALS, which has been shown to also inhibit voltage-dependent Na + channels, [20][21][22] and tetrodotoxin, a poison from the puffer fish that is highly specific for voltage-gated Na + channels. 23,24 Finally, we were interested in whether other AEDs could also protect against NRHypo neurotoxicity. We, therefore, studied felbamate and gabapentin, two AEDs whose mechanism of action is less clear, 25 as well as ethosuximide, an AED which is not known to interact with voltage-gated Na + channels but instead inhibits the low threshold type of transient calcium current (T-type current).…”
Section: Molecular Psychiatrymentioning
confidence: 99%